Preliminary delivery efficiency prediction of nanotherapeutics into crucial cell populations in bone marrow niche - Huijuan Chen; Anzhi Hu; Mengdi Xiao; Shiyi Hong; Jing Liang; Quanlong Zhang; Yang Xiong; Mancang Gu; Chaofeng Mu (Elsevier, 2023)
Several crucial stromal cell populations regulate hematopoiesis and malignant diseases in bone marrow niches. Precise regulation of these cell types can remodel niches and develop new therapeutics. Multiple nanocarriers have been developed to transport drugs into the bone marrow selectively. However, the delivery efficiency of these nanotherapeutics into crucial niche cells is still unknown, and there is no method available for predicting delivery efficiency in these cell types. Here, we constructed a three-dimensional bone marrow niche composed of three crucial cell populations: endothelial cells (ECs), mesenchymal stromal cells (MSCs), and osteoblasts (OBs). Mimetic niches were used to detect the cellular uptake of three typical drug nanocarriers into ECs/MSCs/OBs in vitro. Less than 5% of nanocarriers were taken up by three stromal cell types, and most of them were located in the extracellular matrix. Delivery efficiency in sinusoidal ECs, arteriole ECs, MSCs, and OBs in vivo was analyzed. The correlation analysis showed that the cellular uptake of three nanocarriers in crucial cell types in vitro is positively linear correlated with its delivery efficiency in vivo. The delivery efficiency into MSCs was remarkably higher than that into ECs and OBs, no matter what kind of nanocarrier. The overall efficiency into sinusoidal ECs was greatly lower than that into arteriole ECs. All nanocarriers were hard to be delivered into OBs (<1%). Our findings revealed that cell tropisms of nanocarriers with different compositions and ligand attachments in vivo could be predicted via detecting their cellular uptake in bone marrow niches in vitro. This study provided the methodology for niche-directed nanotherapeutics development.